2013
DOI: 10.4103/1947-489x.210537
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and adherence to health advice among adults with diabetes in Libya

Abstract: Knowledge of and Adherence to Health Advice among Adults with Diabetes in Libyahttp://researchonline.ljmu.ac.uk/id/eprint/2208/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
4
5
2
Order By: Relevance
“…An early study of the epidemiological pattern of diabetes in Benghazi, Libya, found that the prevalence of T2DM was significantly higher among females than males ( 27 ). The predominance of females over males was also reported in a previous study among diabetics in the same center where our study was conducted ( 28 ) and in other Libyan diabetes settings ( 6 , 7 ). The respondents reported a low identity perception, indicating that they attributed few of the symptoms they had experienced after the diagnosis to their diabetes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…An early study of the epidemiological pattern of diabetes in Benghazi, Libya, found that the prevalence of T2DM was significantly higher among females than males ( 27 ). The predominance of females over males was also reported in a previous study among diabetics in the same center where our study was conducted ( 28 ) and in other Libyan diabetes settings ( 6 , 7 ). The respondents reported a low identity perception, indicating that they attributed few of the symptoms they had experienced after the diagnosis to their diabetes.…”
Section: Discussionsupporting
confidence: 87%
“…The issue of low therapeutic adherence in chronic diseases is generally greater in developing countries than in developed countries ( 5 ). In Libya, a previous study among diabetics at Benghazi Diabetes Centre reported a considerable rate of suboptimal medication adherence ( 6 ), and a more recent study in the same center found that non-adherence to diabetes management advice as measured by glycosylated hemoglobin level was considerable ( 7 ). Therefore, there is a need to identify the factors that could influence medication adherence among Libyan diabetic patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predominance of females over males was probably merely a reflection of the sex pattern of type 2 diabetes (22). As reported in the present study, several other studies among people with diabetes in Libya have shown a preponderance of females over males (23)(24)(25).…”
Section: Discussionsupporting
confidence: 83%
“…Despite all of these aspects, an apparent gap exists between knowledge and the attitude towards diabetes among diabetic patients [10]. Results of studies from different countries including the GCC ones came out with the conclusion that the diabetes knowledge among diabetic patient is poor and not satisfactory [11][12][13][14][15][16][17].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%